2018
DOI: 10.1007/s11682-018-9983-0
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of high magnitude acceleration events predicts cerebrovascular reactivity changes in female high school soccer athletes

Abstract: Accumulation of high magnitude acceleration events predicts cerebrovascular reactivity changes in female high school soccer athletes. Brain imaging and behavior, 1-11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…However, prior research from our group has shown the PCA NVC response remains unchanged following a full season of elite contact-sport participation (13), and is disrupted following acute sport-related concussions (12). Consistent with this notion are the findings from Svaldi et al (45,46) who have examined cerebrovascular reactivity responses to carbon dioxide using magnetic resonance imaging measures (MRI) in female high school and collegiate soccer players. They used MRI scans at pre-season, during the first 5 weeks of the season, in the second half of the season and 1-2 months after the completion of the season while also tracking head impact exposures with the xPatch (22,45) and demonstrated deficits in cerebrovascular reactivity in those participants with the highest cumulative accumulation of linear head impacts (those experiencing 14,487 g vs. 4,511 g over the season).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, prior research from our group has shown the PCA NVC response remains unchanged following a full season of elite contact-sport participation (13), and is disrupted following acute sport-related concussions (12). Consistent with this notion are the findings from Svaldi et al (45,46) who have examined cerebrovascular reactivity responses to carbon dioxide using magnetic resonance imaging measures (MRI) in female high school and collegiate soccer players. They used MRI scans at pre-season, during the first 5 weeks of the season, in the second half of the season and 1-2 months after the completion of the season while also tracking head impact exposures with the xPatch (22,45) and demonstrated deficits in cerebrovascular reactivity in those participants with the highest cumulative accumulation of linear head impacts (those experiencing 14,487 g vs. 4,511 g over the season).…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with this notion are the findings from Svaldi et al (45,46) who have examined cerebrovascular reactivity responses to carbon dioxide using magnetic resonance imaging measures (MRI) in female high school and collegiate soccer players. They used MRI scans at pre-season, during the first 5 weeks of the season, in the second half of the season and 1-2 months after the completion of the season while also tracking head impact exposures with the xPatch (22,45) and demonstrated deficits in cerebrovascular reactivity in those participants with the highest cumulative accumulation of linear head impacts (those experiencing 14,487 g vs. 4,511 g over the season). In conjunction with the current findings, these results suggest soccer heading can dysregulate CBF control mechanisms.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, NIRS can provide real-time cerebral vascular reactivity (CVR) measurements on the football field, as chronic brain damage has prompted concern for contact sport athletes. [27][28][29] Also, NIRS can provide bedside CVR measurements for immobile elderly people. 30,31 However, results from CI tasks have been inconsistent; this may be due to physiological noise coming from skin and skull.…”
Section: -3 7mentioning
confidence: 99%
“…It must be noted that an official diagnosis of concussion is not required for athletes to exhibit substantial changes in brain structure and function that are detectable with a range of assessment tools [11][12][13][14][15][16][17]. Recent work suggests that some aspect of cumulative exposure is the primary risk factor in the development of pathological neurophysiological changes accrued throughout the season in contact sports [11,16,[18][19][20] and that impacts exceeding 50g may be particularly dangerous [21].…”
Section: Introductionmentioning
confidence: 99%